Microalterations in the third eyelid gland of dogs with keratoconjunctivits sicca secondary to distemper - Brito, F.L.C.; Silva Júnior, V.A.; Maia, F.C.L.; Pereira Junior, J.R.; Laus, J.L. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2007)
Analisaram-se, à microscopia óptica, 28 glândulas da terceira pálpebra de cães, que morreram com cinomose. O diagnóstico de ceratoconjuntivite seca baseou-se nas alterações da superfície ocular e no teste da lágrima de Schirmer. À histologia, visibilizaram-se atrofia tubuloacina, espessamento do tecido conjuntivo e exudação inflamatória de leve a intensa com presença de plasmócitos, de histiócitos e por hipertrofia compensatória de algumas glândulas. O lume das glândulas encontrava-se hipertrofiado contendo células epiteliais descamadas, polimorfonucleares e hemácias, além de muco.

Keratoconjunctivitis sicca is characterized by qualitative or quantitative abnormalities in the aqueous component of the tear film and is frequent in dogs with distemper. Twenty-eight third eyelid glands of end-stage dogs that died from distemper were analyzed by light microscopy. Keratoconjunctivitis sicca was diagnosed based on ophthalmic findings regarding alterations in the ocular surface and by the Schirmer tear test. The excised glands were fixed in 10% buffered formalin and processed for embedding in paraffin. The blocks were cut into 4µm sections and the sections were stained with hematoxylin-eosin and Masson's trichrome. Analysis revealed tubuloacinar gland atrophy, thickening of connective tissue, and mild to intense inflammatory exudation mainly characterized by the presence of plasma cells and histiocytes and by compensatory hypertrophy of some glands. The glandular lumen was hypertrophied and contained shedded epithelial cells, polymorphonuclear cells and red blood cells, in addition to mucus.
Microalterações da glândula terceira pálpebra em cães com cinomose e acometido por ceratoconjuntivite seca
Keywords: Dog; distemper; keratoconjunctivitis sicca; third eyelid gland; Cão; Cinomose; Ceratoconjuntivite seca; glândula terceira pálpebra